Correlation between fractional clearance and optical outcomes of LASIK myopia correction - Milivojević, Milorad; Knežević, Snežana; Radojičić, Bojan; Zečević, Rada; Marjanović, Ivan (Medical Gazzette, 2026)
Excimer laser pulses using the LASIK method ablate the corneal stroma, achieving its remodeling to desired optical characteristics. Besides correcting ametropia, it is desirable to minimize the induction of higher-order optical aberrations (HOA), as they affect the occurrence of glare and halos in night vision conditions. Fractional clearance (FC) represents the ratio of the treated optical zone (OZ) diameter to the pupil diameter in scotopic lighting conditions. The aim of this study is to examine the relationship between the enlargement of the treated OZ diameter and the increase in FC index on postoperative HOA levels. A prospective study included 37 subjects (74 eyes) with myopia treated with the LASIK method. The eye with higher residual stromal bed value was treated with an OZ diameter of 7.0 mm, and the other eye of the same patient with an OZ diameter of 6.5 mm. After 6 months, objective evaluation of optical outcomes was performed using an Analyzer device. The mean FC value in the group of eyes treated with OZ 6.5 mm is 2.138 (SD 0.30), and in the group treated with OZ 7.0 mm is 2.325 (SD 0.37), with a statistically highly significant difference (t=3.64; p
Keywords: fractional clearance; optical zone; LASIK; higher-order optical aberrations